Financial data analytics: With machine learning, optimization and statistics - Chen, Sam; Cheung, Ka Chun; Yam, Phillip (New Jersey John Wiley & sons, Inc., 2025)
An essential introduction to data analytics and Machine Learning techniques in the business sector In Financial Data Analytics with Machine Learning, Optimization and Statistics, a team consisting of a distinguished applied mathematician and statistician, experienced actuarial professionals and working data analysts delivers an expertly balanced combination of traditional financial statistics, effective machine learning tools, and mathematics.